Evaluation of certain botanicals for eco-friendly management of red flour beetle, Tribolium castaneum (Hbst.) infesting stored sesame: Evaluation of certain botanicals for eco-friendly management of red flour beetle, Tribolium castaneum (Hbst.) infesting stored sesame - B SUNDAR; RASHMI VISHWAKARMA; P DURAIMURUGAN; A K BHOWMICK (Journal of Oilseeds Research, 2023)
The experiment was conducted to assess the effectiveness of different botanicals for the eco-friendly management of red flour beetle (Tribolium castaneum) infesting stored sesame. The effectiveness of the botanicals was assessed based on the parameters viz., per cent seed damage, per cent weight loss, number of adults emerged and germination percentage at 6 months after storage. From this study, it was observed that the treatment sweet flag rhizome powder @ 10 g/kg sesame seeds recorded the lowest number of adult emerging (2.3 adults), the lowest percentage of seed damage (11.7%), percentage of seed weight loss (2.9%) and highest percentage germination (74.7%) after six months of storage. Therefore, it can be concluded that sweet flag rhizome powder @ 10 g/kg was the most effective eco-friendly method to manage red flour beetle beetle on stored sesame.